Kemampuan Menulis Naskah Drama Pada Kelas VIII C SMP Negeri 7 Tasikmalaya - Astri Fauziah Hindasah; Dian Khoerani; Risqi Sri Mulyati; Savadila Adinda Mynur; Adita Widara Putra (Pusat Riset dan Inovasi Nasional, 2024)
Literature, created in a creative and innovative way through writing or printing, is beautiful and essential to the teaching of the Indonesian language. The authors of this study use a qualitative descriptive approach. In other words, any symptoms that appear or appear will be recorded based on the current state of affairs. The skills of the student are essential to develop the skills acquired, such as writing skills, because writing is an act or activity that produces writing.